2022
DOI: 10.1108/ijcma-02-2022-0045
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences, job demands and job resources as boundary conditions for relations between experienced incivility and forms of instigated incivility

Abstract: Purpose Using the job–demands resources model as a guide, this study aims to expand the understanding of the boundary conditions of the relation between experienced incivility and instigated incivility. The authors do so by focusing on the unique forms of instigated incivility: hostility, gossip, exclusionary behavior and privacy invasion. Drawing from past research, the authors focus on the personal resources of agreeableness and conscientiousness as individual difference boundary conditions, and the job dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 105 publications
(207 reference statements)
0
3
0
Order By: Relevance
“…It is those “aspects of the job that require sustained physical or mental effort and are therefore associated with certain physiological and psychological costs” ( Demerouti et al, 2001 ; p. 501). Examples include high work pressure, an unfavorable physical environment, emotionally demanding interactions with clients, organizational constraints, and workload perceptions ( Bakker & Demerouti, 2017 ; Hughes & Jex, 2022 ).…”
Section: Theoretical Perspective and Hypothesesmentioning
confidence: 99%
“…It is those “aspects of the job that require sustained physical or mental effort and are therefore associated with certain physiological and psychological costs” ( Demerouti et al, 2001 ; p. 501). Examples include high work pressure, an unfavorable physical environment, emotionally demanding interactions with clients, organizational constraints, and workload perceptions ( Bakker & Demerouti, 2017 ; Hughes & Jex, 2022 ).…”
Section: Theoretical Perspective and Hypothesesmentioning
confidence: 99%
“…In line with the JD-R framework, when job demands escalate, job resources become increasingly crucial because they aid employees in the attainment of their workplace objectives (Bakker and Demerouti, 2007). The degree of constructive interpersonal interaction offered by colleagues and superiors is called workplace social support (Jonsdottir and Kristinsson, 2020), which is one of the widely recognised job resources (Hughes and Jex, 2022; Jolly et al , 2021). Social support may be provided by offering guidance, listening and displaying empathy or trustworthiness in the workplace (Jonsdottir et al , 2020; Jonsdottir and Kristinsson, 2020).…”
Section: Theoretical Underpinningmentioning
confidence: 99%
“…Beginning with agreeableness, recent research (e.g. Hughes & Jex, 2022; Welbourne et al, 2020) has found that this trait may strengthen relations between interpersonal stressors and psychological strains, due to these stressors breaching agreeable employees' desire for harmony. When confronted with situations that disrupt social harmony (e.g.…”
Section: Introductionmentioning
confidence: 99%